Presidente de la Municipalidad de Maynas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: La fotografía muestra al presidente de la municipalidad de Maynas Roni Valera dando una entrevista para una emisora de la zona.
ENGLISH: The photograph shows the president of the municipality of Maynas Roni Valera giving an interview for a local radio station.

SPANISH: La fotografía muestra al presidente de la municipalidad de Maynas Roni Valera dando una entrevista para una emisora de la zona.
ENGLISH: The photograph shows the president of the municipality of Maynas Roni Valera giving an interview for a local radio station.
President of the Municipality of Maynas
Keywords: Iquitos (Perú)|~|Actividades culturales|~|Perú|~|Perú--Cultura Amazónica|~|Perú--Personajes Religiosos